Analisis Kinerja PDAM Kota Padang Panjang dalam memberikan Pelayanan Air Bersih untuk Masyarakat Kota Padang Panjang - Citra Dwi Putri; Kusdarini Kusdarini; Roni Ekha Putera (Jurnal Public Policy, 2021)
This research is motivated by the large number of water resources owned by PDAM Padang Panjang city. Furthermore, PDAM Padang Panjang city also has a breakthrough in activities that are not owned by other PDAMs in the West Sumatra region. Nevertheless, in reality, PDAM Padang Panjang City has not provided the same service to all its service areas. The research objective is to describe the performance of PDAM Padang Panjang in providing clean water for the people of Padang Panjang City. The research method used in this research is descriptive qualitative with data collection techniques using interviews, observation, and documentation. To test the validity of the data obtained, it was carried out through source triangulation techniques. The theory used in this research is the theory of performance, according to Wibowo, which consists of four variables, namely input, process, output, and benefits. The results showed that from the four variables put forward by Wibowo, it could be concluded that the performance of PDAM Padang Panjang in providing clean water for the people of Padang Panjang has not been maximally achieved. Because there are still several indicators from the theory used that have not achieved the results expected by the PDAM. For example, the human resources in the PDAM have not received evenly distributed training, incomplete financial management, incomplete supporting documents, and the management of existing natural water sources has not been maximized.